The secret place - French, Tana (New York: Viking, 2014)
The photo on the card shows a boy who was found murdered, a year ago, on the grounds of a girls' boarding school in the leafy suburbs of Dublin. The caption says "I know who killed him".
Keywords: Detectives -- Ireland -- Dublin -- Fiction; Detective and mystery stories; Murder -- Investigation -- Fiction